2019
DOI: 10.1016/j.ejca.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of carboplatin AUC-10 guided by positron emission tomography–defined metabolic response in metastatic seminoma

Abstract: Conclusion Carboplatin AUC 10 monotherapy is effective with low toxicity. Early changes during PET scanning may allow de-escalation of therapy in high volume diseasecomparison against combination therapy is warranted. Clinicaltrials.gov identifier: NCT02272816

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Considering the alternative advanced relapse definition ($ 3 cm), the increase associated with the three-scan schedule was small (six events, 2.0% increase, ITT) and noninferiority was demonstrated. Thus, the impact of a less frequent imaging schedule on the selection for the use of local treatment at relapse (either radiotherapy or, as recently reported, minimally invasive retroperitoneal surgery 31,32 ) is likely to be small, especially as our data suggest some centers use the same approach (either highdose carboplatin 23 or BEP) regardless of relapse stage/size. Hence, numbers of advanced relapses would not affect care.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Considering the alternative advanced relapse definition ($ 3 cm), the increase associated with the three-scan schedule was small (six events, 2.0% increase, ITT) and noninferiority was demonstrated. Thus, the impact of a less frequent imaging schedule on the selection for the use of local treatment at relapse (either radiotherapy or, as recently reported, minimally invasive retroperitoneal surgery 31,32 ) is likely to be small, especially as our data suggest some centers use the same approach (either highdose carboplatin 23 or BEP) regardless of relapse stage/size. Hence, numbers of advanced relapses would not affect care.…”
Section: Discussionmentioning
confidence: 68%
“…Relapses were treated with low-dose carboplatin and paraaortic radiotherapy (33), combination chemotherapy (normally 43 BEP, 28), or high-dose carboplatin (17; Appendix Fig A2, online only). 23 Combination chemotherapy was slightly more common in the three-scan group, given the greater number of advanced relapses. Sixtyseven/80 (84%) of patients had a complete response (in Abbreviations: CT, computed tomography; ITT, intention-to-treat; MRI, magnetic resonance imaging; PP, per-protocol.…”
Section: Relapse Treatment and Long-term Outcomesmentioning
confidence: 98%
“…Local control duration ranged from 5 to 12 months, and the median PFS time was 8 months. Studies have also shown that carboplatin can be used as an alternative to cisplatin-based combination chemotherapy to reduce the incidence of pulmonary toxicity, neurological damage and renal toxicity ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bei fehlender metabolischer Aktivität wurden 2 weitere Zyklen Carboplatin AUC10 verabreicht, bei PET-Positivität waren es 3 weitere Zyklen. Die Autoren berichteten über ein PFS von etwa 95 % [26]. Limitierend ist die Größe der Studie mit lediglich knapp 50 Patienten und die mediane Follow-up-Dauer von etwa 2,5 Jahren.…”
Section: Chemotherapieunclassified